PENERAPAN COOKING CLASS BERBAHAN DASAR TEMPE UNTUK MENINGKATKAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI KB AGUNG KENCANA RANDUAGUNG SINGOSARI - Wantini; Siti Muntomimah; Sarah Emmanuel Haryono (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
The development of fine motor skills in early childhood tends to progress more slowly than gross motor skills, thus requiring continuous stimulation to reach optimal growth. Children with well-developed fine motor skills generally perform better in academic areas such as writing and arithmetic. This study aims to examine the implementation of a tempe-based cooking class activity in improving the fine motor skills of children aged 5–6 years at KB Agung Kencana Randuagung Singosari, involving 20 students as subjects. The research employed the Classroom Action Research (CAR) method using the spiral model by Kemmis and McTaggart, consisting of planning, action, observation, and reflection stages carried out over two cycles. The researcher acted as a facilitator and active observer, collaborating with the teacher. The observed indicators of fine motor skills included the children's ability to grate, squeeze, mix, and shape tempe dough. The results showed a significant improvement from an average of 54% in the pre-cycle stage to 91% by the end of the second cycle. This demonstrates that cooking classes using local ingredients such as tempe not only provide enjoyable learning experiences but are also effective in enhancing children’s manipulative skills. Future research is recommended to explore other local materials as learning media to support various aspects of early childhood development. Keywords:  early childhood; fine motor skills; cooking class